How personal factors grow students' interest in entrepreneurship - Arief Dwi Saputra; Alfina Rahmatia; Muslimah Muslimah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
This study investigates how personal factors can influence entrepreneurship's interest in terms of cognitive variables with indicators of skills and knowledge, affective variables with indicators of attitude and value, and conative variables with indicators of behavior and experience. This study uses a quantitative strategy through a sample of 338 informants. The root of the problem is reviewed from the literature review and strengthened by data collection from the online interview process. Based on these results, personal factors through related variables and indicators can be used as a research agenda to answer corporate contributions problems that offer answers related to reasons for entrepreneurship. The implication is aimed as a strategy to foster student interest in entrepreneurship by showing a close relationship that is mutually supportive and relevant from contributing to each variable related to personal factors. This study also provides a scientific contribution in the form of knowledge about an entrepreneurial interest created from personal factors.